2023
DOI: 10.1200/jco.23.00857
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Oncology Care of Symptoms of Anxiety and Depression in Adults With Cancer: Society for Integrative Oncology–ASCO Guideline

Linda E. Carlson,
Nofisat Ismaila,
Elizabeth L. Addington
et al.

Abstract: PURPOSE To provide evidence-based recommendations to health care providers on integrative approaches to managing anxiety and depression symptoms in adults living with cancer. METHODS The Society for Integrative Oncology and ASCO convened an expert panel of integrative oncology, medical oncology, radiation oncology, surgical oncology, palliative oncology, social sciences, mind-body medicine, nursing, methodology, and patient advocacy representatives. The literature search included systematic reviews, meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 205 publications
0
5
0
Order By: Relevance
“…Patients with cancer are disproportionately afflicted with anxiety and depression, with estimated prevalence rates of 18% and 20%, respectively. 38 The most recent American Society of Clinical Oncology guidelines on the management of anxiety and depression in patients with cancer still refer to digital health interventions such as telehealth as a "future direction"; we anticipate that this will be an area for increased and early adoption of telehealth technology. Telehealth applications also may find a role in supporting the developmental and social needs of children, adolescents, and young adults with cancer, particularly those living in rural or isolated settings.…”
Section: Guided Interventionsmentioning
confidence: 99%
“…Patients with cancer are disproportionately afflicted with anxiety and depression, with estimated prevalence rates of 18% and 20%, respectively. 38 The most recent American Society of Clinical Oncology guidelines on the management of anxiety and depression in patients with cancer still refer to digital health interventions such as telehealth as a "future direction"; we anticipate that this will be an area for increased and early adoption of telehealth technology. Telehealth applications also may find a role in supporting the developmental and social needs of children, adolescents, and young adults with cancer, particularly those living in rural or isolated settings.…”
Section: Guided Interventionsmentioning
confidence: 99%
“…The hallmarks of many mind–body interventions are mindfulness and intention to berating, gentle touch, movement, and spirituality. Recent IO-related clinical guidelines on pain, depression, and anxiety co-published by the Society for Integrative Oncology (SIO) and the American Society of Clinical Oncology (ASCO) recommend mind–body medicine for the following indications: hypnosis in patients who experience procedural pain; MBIs, yoga, relaxation, and music therapy for treating symptoms of anxiety during active treatment; MBIs, yoga, tai chi, and/or qigong for treating anxiety symptoms after cancer treatment; MBIs, yoga, music therapy, and relaxation for depression symptoms during oncology treatment; and MBIs, yoga, and tai chi and/or qigong post-treatment depression [ 102 , 103 ]. In the field of Multiple Myeloma, Lamers et al, reported that as many as 52% of patients desired psychosocial interventions near diagnosis, where relaxation techniques were the most common preferred modality reported by 21% of patients [ 104 ].…”
Section: Mind–body Medicinementioning
confidence: 99%
“…Although there is some evidence supporting the use of a few dietary supplements for treatment of depression and anxiety in the general population, 25 there is inconclusive evidence that those supplements are safe and effective for people diagnosed with cancer. 10 Furthermore, some supplements used for anxiety or depression may pose high risk of supplement-drug interactions, such as Kava Kava (Piper methysticum) and St Johns Wort (Hypericum perforatum), 26,27 which could be especially detrimental for patients engaged in active cancer treatment.…”
Section: Question: What Should I Tell a Patient Asking About The Use ...mentioning
confidence: 99%